La educación en derechos humanos con personas privadas de libertad de una Unidad de Atención Integral en Costa Rica - Fernández Masis, Andrey; Torres Ramírez, Gerald; Naranjo Segura, Juan Carlos (Universidad de Costa Rica, 2024)
This research arises from the Final Graduation Project to opt for the Bachelor's degree in Teaching Social Studies and Civic Education at the University of Costa Rica. This seeks to describe the role of Human Rights Education in the imprisonment experience of ninth-year incarcerated students based on the knowledge of their rights, duties and norms, in the Reynaldo Villalobos Zúñiga Comprehensive Care Unit, in Alajuela, Costa Rica, during the 2021-2022 school year. For this, a qualitative approach of exploratory scope is carried out through the use of the in-depth interview information collection technique, with three students from the Integrated Center for Adult Education (CINDEA), located within the Reynaldo Villalobos Zúñiga penitentiary center. The main results show the positive impact of human rights education for the student deprived of liberty, promoting the development of theoretical and coexistence tools, development of values and attitudes in the search for the defense of their rights, healthy coexistence and skills to reintegration process. It is concluded that the role of the EDH has been notably positive since it promotes a critical position towards respect for rights within the penal center.